2022
DOI: 10.21203/rs.3.rs-2364358/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of social influences on infant food consumption in the city of Ouagadougou (Burkina Faso): a retrospective survey

Abstract: Background From the age of 6 months, children need, in addition to breast milk, a complementary food with nutritional composition that meets their needs. In addition, the lack of adaptation of some children to family feeding conditions could be sources of malnutrition. In Burkina Faso, little information’s are available on children's consumption of family foods. The objective was therefore to describe the feeding habits and frequencies of infants aged from 6 to 23 months. Methods The study consisted in colle… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…A study in Ethiopia found out that only 20% of households consumed eggs one to two times per week (Daba et al, 2021). Another study in Burkina Faso found out that eggs were amongst the least consumed foods in 618 children studied and only 6.6% women gave eggs to their breastfed children (Bougma et al, 2023).…”
Section: Barriers To Egg Consumption and Solutionsmentioning
confidence: 99%
“…A study in Ethiopia found out that only 20% of households consumed eggs one to two times per week (Daba et al, 2021). Another study in Burkina Faso found out that eggs were amongst the least consumed foods in 618 children studied and only 6.6% women gave eggs to their breastfed children (Bougma et al, 2023).…”
Section: Barriers To Egg Consumption and Solutionsmentioning
confidence: 99%